The Relationship Between Attachment to God, Prosociality, and Image of God - Bayramoglu, Yunus (Archive for the psychology of religion, 2018)
Although religiosity fosters some antisocial behaviors (e.g., support for suicide attacks), it is well-known that it also enhances in-group cooperation and prosociality (e.g., donating to charity). Supernatural punishment hypothesis suggests that the fear of punishment from an invisible, potent, and powerful supernatural agent can keep everyone in line, and encourage prosociality. We first investigated this relationship in a predominantly Muslim country and then tested a model suggesting that attachment to God can lead people to think God as authoritarian, which in turn leads them to report more prosocial intentions. The results demonstrate that (1) there are some findings suggesting that Attachment to God Inventory is a reliable measure in Turkey, (2) seeing God as authoritarian is positively correlated with prosociality, and (3) our above-mentioned model was supported by the data. Results generally support the supernatural punishment hypothesis and additionally show the utility of attachment theory in explaining the religiosity-prosociality link.